2015
DOI: 10.1177/1687814015578361
|View full text |Cite
|
Sign up to set email alerts
|

A model predictive control approach combined unscented Kalman filter vehicle state estimation in intelligent vehicle trajectory tracking

Abstract: Trajectory tracking and state estimation are significant in the motion planning and intelligent vehicle control. This article focuses on the model predictive control approach for the trajectory tracking of the intelligent vehicles and state estimation of the nonlinear vehicle system. The constraints of the system states are considered when applying the model predictive control method to the practical problem, while 4-degree-of-freedom vehicle model and unscented Kalman filter are proposed to estimate the vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 25 publications
(28 reference statements)
0
23
0
Order By: Relevance
“…Yu et al used unscented Kalman filter to estimate vehicle state and designed MPC controller based on the estimated vehicle state. 24 The simulation results verified the effectiveness and robustness of state estimation and path tracking. Ercan et al considered the dynamics of vehicle steering system and identified the parameters of steering system model online with recursive least squares algorithm.…”
Section: Introductionmentioning
confidence: 66%
“…Yu et al used unscented Kalman filter to estimate vehicle state and designed MPC controller based on the estimated vehicle state. 24 The simulation results verified the effectiveness and robustness of state estimation and path tracking. Ercan et al considered the dynamics of vehicle steering system and identified the parameters of steering system model online with recursive least squares algorithm.…”
Section: Introductionmentioning
confidence: 66%
“…The diagram of hierarchical behavior representation in the numerical case. There are four high-level behaviors I, II, III and IV which are composed of three of the five stages A, B, C, D and E while each of these stages can also be separated into two of the six sub-stages (1)- (6). The order of stages and sub-stages are fixed in each high-level behavior.…”
Section: Generic Tracking and Prediction Frameworkmentioning
confidence: 99%
“…4. If the vehicle vibration, roll, pitch and other secondary factors are ignored, and the height of vehicle gravity center is h, steering angle is α, then the vehicle dynamics model is simplified as equation (8) to (13) (16,17) . − ( 1 + 2 ) + 3 + 4 (9) = 1 + 2 + 3 + 4 (10)…”
Section: Dynamics Model Of Vehiclementioning
confidence: 99%